THE EFFECT OF COVID-19 CRISIS ON CHRONIC DISEASE TRACKING: BRIDGING A DATA GAP - Rajkovic, Petar; Milenković, Aleksandar; Đorđević, Anđelija; Janković, Dragan (Acta medicae Medianae, 2024)
COVID-19 negatively shifted chronic disease tracking and general data collection in primary healthcare facilities. The focus was moved to support the counter-pandemic efforts, while the number of registered general examinations and those dedicated to chronic diseases dropped. In that light, the results of the algorithms dedicated to helping identify potential new chronic patients become less relevant. With a lower number of registered visits, the results of the estimate become less relevant with the increased number of unidentified patients with chronic medical cases. This research aims to improve the existing data summarization methods and increase their relevance by adding new criteria, using the potential to integrate with other medical information systems, and making them more configurable up to the patient level. The updated data aggregation tools are evaluated against results collected in Niš Primary and Ambulatory Care Center and compared with the results from the initial version of the algorithm.